Komunikasi di Media Sosial: Perspektif Kesetaraan Gender - Syayekti, Ela Indah Dwi (Academic Journal of Da'wa and Communication, 2023)
Mass media and social media generally use women as the subject and object of their content. Unfortunately, the exploitation is unbalanced and even impressive, only making women an object to be seen from the feminine side. The aim of this research is to explain the creation of communication in the media, especially social media, from a gender perspective. This research uses a qualitative approach with a library study method. The results shows that gender-sensitive social media communications can be achieved by: 1) strengthening digital literacy for the public, building a networked digital community to strengthen gender empowerment and content through education and social media discussion spaces; 2) educating about women's needs in the fields of politics, social, cultural, and violence using gender-friendly language; 3) presenting gender-neutral social media content or posts by showing individuals as subjects; and 4) engaging men to break the culture of patriarchy through equal communication.